Thin Films of Tungsten Disulfide Grown by Sulfurization of Sputtered Metal for Ultra-Low Detection of Nitrogen Dioxide Gas - Anastasiya D. Fedorenko; Svetlana A. Lavrukhina; Victor A. Alekseev; Vitalii I. Sysoev; Veronica S. Sulyaeva; Alexander V. Okotrub; Lyubov G. Bulusheva (Nanomaterials)
Tungsten disulfide (WS2) is attractive for the development of chemiresistive sensors due to its favorable band gap, as well as its mechanical strength and chemical stability. In this work, we elaborate a procedure for the synthesis of thin films consisting of vertically and/or horizontally oriented WS2 nanoparticles by sulfurizing nanometer-thick tungsten layers deposited on oxidized silicon substrates using magnetron sputtering. According to X-ray photoelectron spectroscopy and Raman scattering data, WS2 films grown in an H2-containing atmosphere at 1000 °C are almost free of tungsten oxide. The WS2 film’s thickness is controlled by varying the tungsten sputtering duration from 10 to 90 s. The highest response to nitrogen dioxide (NO2) at room temperature was demonstrated by the film obtained using a tungsten layer sputtered for 30 s. The increased sensitivity is attributed to the high surface-to-volume ratio provided by the horizontal and vertical orientation of the small WS2 nanoparticles. Based on density functional calculations, we conclude that the small in-plane size of WS2 provides many high-energy sites for NO2 adsorption, which leads to greater charge transfer in the sensor. The detection limit of NO2 calculated for the best sensor (WS2-30s) is 15 ppb at room temperature and 8 ppb at 125 °C. The sensor can operate in a humid environment and is significantly less sensitive to NH3 and a mixture of H2, CO, and CO2 gases.